Infection Control in Dental Settings During Management of Medically Compromised Patients: A Systematic Review - Salah Etwati (AlQalam Journal of Medical and Applied Sciences, 2025)
Medically compromised patients present unique challenges in dental care due to increased susceptibility to infections and complications. Effective infection control protocols are paramount to ensuring patient safety and preventing cross-transmission. This systematic review synthesized current evidence on infection control practices specifically tailored for the dental management of patients with cardiovascular disease, renal disorders, asthma, epilepsy, hypertension, and diabetes. The study was conducted in accordance with PRISMA guidelines across PubMed/MEDLINE, Scopus, Web of Science, and the Cochrane Library (2015-2024). Inclusion criteria encompassed studies addressing infection control in dental settings for medically compromised populations. Quality assessment was performed using appropriate methodological tools. From 1,247 identified records, 78 studies met the inclusion criteria. Key findings identified five critical domains: (1) Comprehensive patient assessment and risk stratification; (2) Rigorous personal protective equipment protocols; (3) Validated instrument sterilization processes; (4) Systematic environmental infection control; and (5) Condition-specific modifications. Diabetic patients demonstrated significantly higher infection risks (OR=2.3, 95% CI: 1.8-3.0), while cardiovascular patients required enhanced aseptic techniques to prevent bacteremia. Effective infection control for medically compromised dental patients requires an integrated, multi-layered approach combining universal precautions with condition-specific adaptations. Standardized protocols, continuous staff training, and regular auditing are essential components of a robust infection prevention strategy. Future research should focus on protocol implementation outcomes and cost-effectiveness analyses.